2006
DOI: 10.1369/jhc.5c6813.2006
|View full text |Cite
|
Sign up to set email alerts
|

LIM Kinase 2 Is Widely Expressed in All Tissues

Abstract: S U M M A R Y The LIM kinase family includes two proteins: LIMK1 and LIMK2. These proteins have identical genomic structure and overall amino acid identity of 50%. Both proteins regulate actin polymerization via phosphorylation and inactivation of the actin depolymerizing factors ADF/cofilin. Although the function of endogenous LIMK1 is well established, little is known about the function of the endogenous LIMK2 protein. To understand the specific role of endogenous LIMK2 protein, we examined its expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 31 publications
(50 reference statements)
0
48
0
2
Order By: Relevance
“…Immunoprecipitation was performed as described earlier (Acevedo et al, 2006). Briefly, whole cell lysates were precleared with protein-G sepharose beads coupled with 2 mg anti-rat IgG2a to remove non-specific binding proteins.…”
Section: Immunoprecipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoprecipitation was performed as described earlier (Acevedo et al, 2006). Briefly, whole cell lysates were precleared with protein-G sepharose beads coupled with 2 mg anti-rat IgG2a to remove non-specific binding proteins.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…Equal amounts of protein (15-50 mg) were resolved on 12% sodium dodecyl sulfatepolyacrylamide gel electrophoresis or 4-20% pre-cast Criterion Tris-HCl gel (Bio-Rad, Hercules, CA, USA) before electrotransfer. Immunoblotting was performed using anti-LIMK2 mAb (Acevedo et al, 2006), anti-GAPDH (Abcam, Cambridge, UK), anti-b-actin (Sigma-Aldrich), anti-p-LIMK1 (Thr508)/ LIMK2 (Thr505) (Cell Signaling, Beverly, MA, USA), anti-pcofilin (phospho-Ser3), anti-cofilin (Abcam, Cambridge, UK) and anti-g-actin (a gift from P Gunning, University of New South Wales, Australia). The membranes were incubated with HRP-conjugated IgG secondary antibodies and proteins detected with ECL Plus (GE Healthcare Life Sciences, Uppsala, Sweden).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Practically nothing is known about the regulatory mechanisms involved in the organization of these Golgi filaments and about how these mechanisms contribute to the generation of specific cargo routes exiting the Golgi complex. A clue to actin filament organization at the Golgi may lie in recent studies on LIM kinases (LIMK) 1 and 2, widely expressed down-regulators of the actin-severing activity of cofilin that in neurons are known to operate downstream of cdc42 and PAK1 (Bamburg, 1999; Foletta et al., 2004;Acevedo et al, 2006). Importantly, a study in hypocampal neurons (Rosso et al, 2004) showed that LIMK1 localizes to the Golgi complex via its LIM domains and to axonal growth cones via its postsynaptic density 95/disclarge/zona occludens domains and that overexpression of LIMK1 promotes axonal growth and differentiation.…”
mentioning
confidence: 99%
“…An-ti-α-tubulin (T5168), acetyl-α-tubulin (Lys40; T6793) and HDAC6 (SAB1406911) antibodies were purchased from Sigma-Aldrich. Additional antibodies used were TPPP1 [6], LIMK1 [12], LIMK2 [15], Flag 9H1 clone [16] and c-myc tag clone 4A6 (Upstate). Immunoblot quantification was performed using the ImageQuant software.…”
Section: Immunoblottingmentioning
confidence: 99%